La représentation du corps féminin : ostracisme, stéréotypes et concupiscence dans David’s Story de Zoë Wicomb - Khella, Férial (Études littéraires africaines)

(untitled) (Association pour l'Étude des Littératures africaines (APELA), 2014)
This article explores Zoë Wicomb’s complex representation of the Black female body in her first novel David’s Story, which deals mainly with the condition of the female guerrilla fighter during and after the struggle for liberation. These women warriors have served the nation and have contribu-ted to its liberation through their bodies, but have also been silenced and ignored in the post-apartheid era. In addition, they have been subjected to multiple forms of physical and sexual violence by their own comrades within the Anti-apartheid Movement. The Black female body, as it appears in the novel, is a site of power, oppression, violence, and even complicity. The pre-sent work tasks itself, firstly, with analyzing not only how the author deconstructs the stereotypical images of the strong female guerrilla but also those concerning Coloured women’s bodies which have been marked by racial and sexual differences, focusing here especially on the question of concupiscence. Then, I will concentrate on the way the female body is represented and inscribed in language. Finally, I will analyze Zoë Wicomb’s narrative techniques by considering the impossibility of representing the body in the absence of discourse.